2018
DOI: 10.1002/advs.201801566
|View full text |Cite
|
Sign up to set email alerts
|

Accessing MHz Operation at 2 V with Field‐Effect Transistors Based on Printed Polymers on Plastic

Abstract: Organic printed electronics are suitable for the development of wearable, lightweight, distributed applications in combination with cost‐effective production processes. Nonetheless, some necessary features for several envisioned disruptive mass‐produced products are still lacking: among these radio‐frequency (RF) communication capability, which requires high operational speed combined with low supply voltage in electronic devices processed on cheap plastic foils. Here, it is demonstrated that high‐frequency, l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 73 publications
(171 reference statements)
4
35
0
Order By: Relevance
“…The responses at different V D and V Bias values are plotted in Figure c,d. The maximum observed oscillation frequency, f osc , is 1.9 kHz with V D = 3 V and V Bias = 2.75 V . Considering the five‐stage ring oscillator rule, the stage delay is 50 μs, which is consistent with the data obtained from the discrete inverter dynamic response.…”
Section: Resultssupporting
confidence: 83%
“…The responses at different V D and V Bias values are plotted in Figure c,d. The maximum observed oscillation frequency, f osc , is 1.9 kHz with V D = 3 V and V Bias = 2.75 V . Considering the five‐stage ring oscillator rule, the stage delay is 50 μs, which is consistent with the data obtained from the discrete inverter dynamic response.…”
Section: Resultssupporting
confidence: 83%
“…The reliability factors for these two devices are both 0.93 (a reliability factor of 1 corresponds to an ideal device) [30]. This reliability factor implies that, even if bad contacts were present, the true mobility of the devices is within 7% of the measured value, and 0.93 is on par with or betters values reported for other systems [31][32][33], with the exception of single crystals [30]. Measurements on a large set of devices (over 100) resulted in a lower average threshold voltage in the flame annealed OFETs, Vth = 2.7 V ± 1.2 V, compared to Vth = 6.2 V ± 1.2 V in the control, suggesting a lower density of traps in these samples.…”
Section: Transistor Characterizationmentioning
confidence: 99%
“…The bias voltage, instead, cannot represent a mean for achieving high‐frequency operation, but should be considered as a specification defined by the target application: while some use‐cases allow for high supply voltage, the majority of portable, stand‐alone devices require the compatibility with thin‐film power sources or energy harvesters. Following such considerations, some authors have recently reported the voltage‐normalized transition frequency f t / V alongside with the simple f t . Since it encompasses the OFET speed performance only in terms of geometrical and physical parameters, f t / V can be considered as a more convenient mean for the comparison of different technologies.…”
Section: Open Challenges In the Route To Ghz Organic Fetsmentioning
confidence: 99%
“…This limitation is related to the parasitism introduced by the characterization setup itself and, only in few cases, the measurement bandwidth was extended to few tens of MHz by adopting inductive probes. Consequently, f t of the most performing OFETs to date was often determined via extrapolation from the data obtained at low frequency, where parasitism is negligible or can be easily accounted for . In the few cases in which inductive probes were used, f t values around 20 MHz have been measured without extrapolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation